Differences in RAAS/vitamin D linked to genetics and socioeconomic factors could explain the higher mortality rate in African Americans with COVID-19 - Martín Giménez, Virna Margarita (2020)
COVID-19 is said to be a pandemic that does not distinguish between skin color or ethnic origin. However, data in many parts of the world, especially in the United States, begin to show that there is a sector of society suffering a more significant impact from this pandemic. The Black population is more vulnerable than the White population to infection and death by COVID-19, with hypertension and diabetes mellitus as probable predisposing factors. Over time, multiple disparities have been observed between the health of Black and White populations, associated mainly with socioeconomic inequalities. However, some mechanisms and pathophysiological susceptibilities begin to be elucidated that are related directly to the higher prevalence of multiple diseases in the Black population, including infection and death by COVID-19. Plasma vitamin D levels and evolutionary adaptations of the renin-angiotensin-aldosterone system (RAAS) in Black people differ considerably from those of other races. The role of these factors in the development and progression of hypertension and multiple lung diseases, among them SARS-CoV-2 infection, is well established. In this sense, the present review attempts to elucidate the link between vitamin D and RAAS ethnic disparities and susceptibility to infection and death by COVID-19 in Black people, and suggests possible mechanisms for this susceptibility.